Innovation in Islamic Education Learning Models - Yanti, Herina; Julian, Marfal; Putri, Nurul Kifani; Akmal, Fauzi; Burhanuddin, Burhanuddin (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2024)
Teachers' success in teaching can be seen from increased student motivation and improved learning outcomes. One of the key factors that support this success is the use of effective teaching strategies. In the context of Islamic religious education, teachers have adopted a combination of strategy mapping and the jigsaw method. This integrated strategy has proven to be effective in providing comprehensive solutions to learning challenges. Not only does it help students master the subject matter, but it also guides them in understanding key concepts deeply, encourages critical and creative thinking, and fosters meaningful peer collaboration. Through strategy mapping, students are able to visualize relationships between concepts, which enhances their cognitive understanding. Meanwhile, the jigsaw strategy trains students to become responsible for their own learning and that of their peers. This method promotes active participation, improves communication skills, teaches the ethics of debate, and instills a sense of respect among students. Furthermore, it nurtures a cooperative spirit as students are encouraged to share knowledge and support each other in the learning process. As a result, the application of these strategies not only increases students’ academic performance but also contributes significantly to their character development, which is a vital component of Islamic religious education.